COPPER-DOPED ALUMINA-PILLARED MONTMORILLONITES AS CATALYSTS FOR OXIDATION OF TOLUENE AND XYLENES WITH HYDROGEN PEROXIDE - Bahranowski K.; Gasior M.; Podobiński J.; Serwicka E.M.; Vartikian L.A.; Kielski A.; Wodnicka K. (My University, 1999)
Catalytic properties of Cu-doped alumina-pillared montmorillonite samples have been tested in the liquid phase oxidation of toluene, o-, m-, and p-xylene with hydrogen peroxide. The results show that the clay samples possess significant activity for both the oxidation of methyl groups and hydroxylation of the aromatic ring. Physicochemical characterization of the catalysts using XRD, BET, ESR and ICP-AES techniques show that they are porous materials with Cu species located in the interlayer, present either as isolated Cu2+ ions anchored at alumina pillars or as patches of amorphous CuO. The dependence of the overall yields on the amount of Cu dopant is discussed and explained in terms of the catalyst structural properties.